ASUHAN KEBIDANAN PADA IBU NIFAS NY “E” P3A0H3 DI KLINIK UTAMA LESTARI TEMBILAHAN TAHUN 2019 - Nurfiarini Julyanti; Ernawati (STIKES HUSADA GEMILANG, 2021)
The puerperium period begins from 2 hours after the birth of the placenta up to 6 weeks (42 days). The most important thing in the postpartum period is the evaluation of the occurrence of bleeding that can causes death for post partum mothers. Puerperium period is a critical period for mothers who have given birth. It is estimated that 60% of maternal deaths occur after childbirth and 50% of them occur within the first 24 hours after childbirt (Indonesian Ministry of Health 2015). The purpose of this midwifery care is to be able to provide comprehensive midwifery care services to post-partum mothers at the Tembilahan Lestari Main Clinic in 2019 through the method of midwifery management approach with varney mindset that is poured in SOAP form. The results obtained from the first until third visit of postpartum conducted from July 18th to August 18th, 2019. The first postpartum visiti conducted in the clinic there was a gap between theory and practice in terms of drug therapy. In the second and third postpartum visits conducted in the patient's home there was no gap between theory and practice. This Final Task Report is expected to be an input material for The Main Lestari Clinic, especially health workers to maintain good performance so that clients remain satisfied with the care provided.